JENIS FRASA PADA CERPEN ORANG-ORANG ANEH DARI SELATAN KARYA NI KOMANG ARIANI - Tia Dwi Fatmawati (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to examine the types of phrases in the short story Orang-Orang Aneh dari Selatan by Ni Komang Ariani using a descriptive qualitative approach. The study focuses on analyzing phrases based on the classification of endocentric and exocentric phrases, as well as further categorization into nominal, verbal, adjectival, prepositional, and numerative phrases. Endocentric phrases are divided into attributive and coordinative types, while exocentric phrases are classified into directive and nondirective types. The results show that the phrases in this short story play a crucial role in constructing sentence meaning and providing additional information about the subject, object, place, time, characteristics, and actions. This study enriches the understanding of phrase theory in linguistics and offers new insights into literary analysis, particularly in terms of using phrases to enrich the narrative. The findings are expected to serve as a reference for future studies in syntax and literary analysis.